Urgensi Pengembangan Koleksi Sebagai Upaya Menyediakan Koleksi yang Berkualitas di Perpustakaan - Iwin Ardyawin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
In the living environment of the library community as an institution providing information services provide easy access to the entire community to access information for free easily and quickly. In the develop- ment stage of the collection of procurement processes gave birth to a quality collection in accordance with the needs of information user and have relevance to the development of the latest information technology so that the library as an information center can compete with other information centers. Collection development policy is a tool / means to direct all activities related to the planning, funding, selection, and procurement of library materials. The collection development policy is also a guide to developing collections directed. In order for the collection development policy can be implemented directed librarian as a waiter of information should always give confidence to library user in using library as source of information.